The Psychological Dynamics of Child with Oppositional Defiant Disorder (ODD) - Musthofa, Wakhid (Utan Kayu Publishing, 2022)
Oppositional defiant disorder (ODD) is one of the often disorders that occur in children. However, malicious and hostile behaviour in children many people called it a child's delinquency. This study aims to describe the psychological dynamics of children with ODD disorders. The research method used is qualitative with a case study approach. The researcher used psychological assessment to collect research data through observation, interviews, and psychological tests on research subjects. The study results are psychological dynamics that cause the emergence of maladaptive behaviours in children with ODD. The results describe four behavioural domains, namely cognitive, emotional, social, and behavioural domains, as the analysis of children behaviour with ODD. By understanding the psychological dynamics of children with behavioural disorders, it is possible to establish a diagnosis, prognosis, and intervention focus given to children with ODD behavioural disorders.